Pengaruh Kualitas Produk, Harga, Promosi Digital Dan Citra Merek Terhadap Keputusan Pembelian Produk Mie Instan Indomie - Al Fani, Fahmiatus Silmiyah; Djaelani, Abdul Kodir; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study was conducted to determine and analyze the influence of product quality, price, digital promotion and brand image on the purchasing decision of Indomie instant noodle products simultaneously and partially on Warmindo consumers in Sidoarjo. The population in the study was the consumer of Warmindo who had purchased Indomie instant noodles at Warmindo at least once, the exact number of which was unknown. The approach method used a non-probability sampling technique, namely purposive sampling, which is a sample collection technique based on certain criteria using a questionnaire distributed to 100 respondents and using the SPSS analysis tool. The results of the study showed that product quality, price, digital promotion and brand image simultaneously influenced the purchasing decision variable of Indomie instant noodle products and partially product quality, price, digital promotion and brand image influenced the purchasing decision variable of Indomie instant noodle products. Keywords: Product Quality, Price, Digital Promotion, Brand Image, Purchasing Decision